(untitled) (MAUSAM, 2000)
NOAA (AVHRR) imageries have been studied for four years from 1982 to 1985. Overlapping wave zones in different imageries of the same fortnight have been given successively higher weightage in the scale of 1 to 7. Different monochromatic hatching scheme for different weight has been adopted. Direction of wind at the level of wave and its wavelength has also been marked over the region. Thus, the climatology has been documented into 24 fortnights. The following two periods emerge, while waves are generally seen over the region. • 16 November to 15 April- This includes Winter Season upto the beginning of pre-monsoon. • 01 June to 15 October -This includes Southwest monsoon upto the third week of postmonsoon. The occurrence of lee waves during the transition period is less. They are the second fortnight of April till the end of May and the second fortnight of October till the middle of November. A scrupulous observation shows that during both the periods (i) and (ii) mentioned above there is systematic eastward shift of the leewave zones with gradual induction of different airmasses over Indian subcontinent from beginning till end. A pictorial representation of the waves over India (West of 90° E Long.) is presented here.